Prenatal diagnosis of micrognathia: a systematic review - Cang, Zhengqiang; Cui, Jiangbo; Pei, Jiaomiao; Wang, Zheng; Du, Yichen; Mu, Siqi; Dou, Wenjie; Fan, Xing; Zhang, Xi; Li, Yang (Frontiers in Pediatrics, 2023)
Purpose: This systematic review aimed to analyze the characteristics of different diagnostic techniques for micrognathia, summarize the consistent diagnostic criteria of each technique, and provide a simple and convenient prenatal diagnosis strategy for micrognathia. Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the search was undertaken in three international databases (PubMed, Scopus, and Web of Science). The three reviewers assessed all papers and extracted the following variables: author’s name and year of publication, country, study design, number of participants, gestational age, equipment for prenatal examination, biometric parameters related to micrognathia, main results. Results: A total of 25 articles included in the analysis. Nineteen articles described cross-sectional studies (76 percent), 4 (16 percent) were case-control studies, and 2 (8 percent) were cohort studies. Fifteen studies (60 percent) had a prospective design, 9 (36 percent) had a retrospective design, and one (4 percent) had both prospective and retrospective design. Thirty-two percent of the studies (n =8) were performed in USA, and the remaining studies were performed in China (n=4), Israel (n=3), Netherlands (n=3), UK (n=1), France (n=1), Italy (n=1), Belgium(n=1), Germany (n=1), Spain (n=1), and Austria (n=1). The prenatal diagnosis of micrognathia can be performed as early as possible in the first trimester, while the second and third trimester of pregnancy were the main prenatal diagnosis period. The articles that were included in the qualitative synthesis describe 30 biometric parameters related to the mandible. Conclusion: Of the 30 biometric parameters related to the mandible, 15 can obtain the simple and convenient diagnostic criteria or warning value for micrognathia. Based on these diagnostic criteria or warning value, clinicians can quickly make a preliminary judgment on facial deformities, to carry out cytologic examination to further clarify the diagnosis of micrognathia.